Smart water: real-time water quality surveillance system / Muhammad Alif Ikram Ayub - Ayub, Muhammad Alif Ikram (2024)
The lack of real-time monitoring of water quality in diverse applications is addressed by the IoT water quality monitoring system. To deliver precise and timely data, the system uses sensors to measure turbidity, pH, and temperature. When water quality deviates from permitted levels, an Arduino Uno microcontroller, which processes the acquired data, activates alarms and messages, controls system functionality. An ESP8266 Wi-Fi module is incorporated into the system for cloud-based monitoring, allowing for remote access to real-time water quality data. The project entails designing and assembling hardware as well as writing, installing, and testing software. Users can efficiently monitor and guarantee the safety of water for drinking, swimming pools, and industrial processes by putting this system into place. Real-time water quality monitoring with the IoT water quality monitoring system is affordable, effective, and contributes to the preservation of clean and safe water supplies